UJI TOKSISITAS AKUT EKSTRAK SELEDRI (Apium graveolens L.) TERHADAP HISTOPATOLOGI HEPAR TIKUS (Sprague dawley) - Putri, Edwina Yunanda (VITEK : Bidang Kedokteran Hewan, 2023)
This study aims to determine acute toxicity effect of celery to histophatology liver of Sprague dawley rat with oral method. Inflammation, degeneration, necrosis and hemorrhage is observed parameters. Maseration is method to extraction with ethanol 70%. Type of this research is Experimental method was conducted by complete random design. The sampel consisted of 24 rats consisting of 4 group namely P0 is control group, P1 treatment with dose 50 mg/kg BB, P2 treatment with dose 500 mg/Kg BB and P3 treatment with dose 5000 mg/kg BB. Treatment given for 14 days. Hepar sample collected by necropsy of all rats method in last day. The sample were processed for tissue processing by Hematoxyllin-eosin method and histopatology examination by using 10x magnificence under the microscope. Data were analyzed by Kruskal-wallis then Mann Whitney test. The results of the analysis showed p≤0,05 in inflammation, degeneration and necrosis parameters. The conclusion of this study is celery extract give influence to histophatology liver was treatment with 500 mg/kg BB in group P2 and dose 5000 mg/kg BB in group 2.